Beat Consumption: The Challenge to Consumerism in Beat Literature - Amien Essif (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
Critics of the Beat generation, from their contemporaries to the present day, often contend that the Beats’ opposition to consumer culture was superficial. Writers like Jack Kerouac, Allen Ginsberg, and William S. Burroughs failed, according to these critics, to present a coherent and principled response to consumerism. This paper, however, argues that while in many ways the Beats continued to participate in consumer culture, they developed a distinct form of consumption—Beat consumption—which attempted to regain sovereignty for the Beat consumer. Through an analysis of Kerouac’s The Dharma Bums and On the Road as well as several of Ginsberg’s seminal works, Beat consumption emerges as a significant concept in the Beat generation’s opposition to the status quo. Though the subsequent cultural revolution of the 1960s produced more radical and clearly articulated critiques of consumerism, the struggle of Beats and Beat writers to reclaim commodities and the act of consuming for their own counterculture was not a failed attempt but a first step.